2020
DOI: 10.1093/geront/gnaa069
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Exposure to Conversion Therapy and Psychosocial Health Among Midlife and Older Adult Men Who Have Sex With Men

Abstract: Background and Objectives Conversion therapies to minimize same-sex attractions are classified as a dangerous practice by numerous scientific institutions in the United States. These practices may contribute to poor long-term psychosocial health, thereby interrupting processes of healthy aging. Few studies have examined psychosocial differences between persons with and without prior experiences of conversion therapy. We assessed associations between prior conversion therapy experiences and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Reports of positive change were stronger and more widely distributed than those of negative change, most strongly for depression, but also for self-esteem, social functioning, self-harm, suicidality, and alcohol/substance abuse. Of note given accounts of increased suicidality due to SOCE exposure (Meanley et al, 2020;Salway et al, 2020), participants in this study reported nine times more (21.8%) marked or extreme positive effects of SOCE on suicidal thoughts or attempts than they reported a similar degree of negative effects (2.4%).…”
Section: Psychological Well-beingmentioning
confidence: 46%
See 2 more Smart Citations
“…Reports of positive change were stronger and more widely distributed than those of negative change, most strongly for depression, but also for self-esteem, social functioning, self-harm, suicidality, and alcohol/substance abuse. Of note given accounts of increased suicidality due to SOCE exposure (Meanley et al, 2020;Salway et al, 2020), participants in this study reported nine times more (21.8%) marked or extreme positive effects of SOCE on suicidal thoughts or attempts than they reported a similar degree of negative effects (2.4%).…”
Section: Psychological Well-beingmentioning
confidence: 46%
“…Examining the recruitment methods and sample characteristics of the aforementioned SOCE studies supports the hypothesis that researchers have likely investigated only one of these sexual minority subgroups at the expense of the other. Samples are often exclusively or mostly dominated by LGB identified participants (Blosnich et al, 2020;Bradshaw et al, 2015;Flentje et al, 2014;Meanley et al, 2020;Ryan et al, 2020;Salway et al, 2020) or by participants with a likelihood of much lower levels of LGB identification given recruitment venues (Jones & Yarhouse, 2011;Karten & Wade, 2010;Spitzer, 2003). SOCE researchers tend to recruit participants through the venues and networks most easily accessible to them; hence, samples usually reflect this selection bias.…”
Section: Harmonizing the Soce Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Examining the recruitment methods and sample characteristics of the aforementioned SOCE studies supports the hypothesis that researchers have likely investigated only one of these sexual minority subgroups at the expense of the other. Samples are often exclusively or mostly dominated by LGB identified participants (Blosnich et al, 2020;Bradshaw et al, 2015;Flentje et al, 2014;Meanley et al, 2020;Ryan et al, 2020;Salway et al, 2020) or by participants with a likelihood of much lower levels of LGB identification given recruitment venues (Jones & Yarhouse, 2011;Karten & Wade, 2010;Spitzer, 2003). SOCE researchers tend to recruit participants through the venues and networks most easily accessible to them; hence, samples usually reflect this selection bias.…”
Section: Effects Of Marriagementioning
confidence: 99%
“…They did find, however, that SOCE in the context of psychiatry and psychotherapy was reported to be moderately to highly effective by 48% and 44% of sample consumers, respectively, although this effectiveness did not seem to be based on experiences of actual change. More recent studies have reported SOCE exposure to be associated with poorer mental health indicators among sexual minority youth (Ryan et al, 2020), adults (Blosnich et al, 2020;Salway et al, 2020), and midlife and older adults (Meanley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%